Development of an Embedded Control System by Means of Dspic Applied in a 4 Dof Robot - Urrea-Onate, E; Kern-Molina, J (IEEE Computer Society, 2016)
In this paper the design and implementation of an embedded control system, using DSCs (Digital Signal Controller) devices of dsPIC type, applied on a four DOF (Degrees Of Freedom) robotic manipulator OWI-535 model is presented. The mathematical model of manipulator is elaborated obtaining joint trajectories to achieve the tracking of a test Cartesian trajectory. A control structure based on a Master/Slave configuration, between two dsPIC30F4013 through SPI (Serial Peripheral Interface) protocol is developed. In such a system, algorithms are implemented: PID (Proportional Integral Derivative) with anti-windup and, generation PWM (Pulse-Width Modulation) and data acquisition, in the DSCs master and slave, respectively. The results are exposed by comparative curves between the desired and real joint trajectories and joint error graphs, generated from real data of the implementation. © 2016 IEEE.